Proximate analysis and oxidative stability of wax from the nuts of Krabok (Irvingia malayana) - Sirisa-Ard P. (International Society for Horticultural Science, 2014)
Proximate analysis and oxidative stability of Krabok nuts were carried out in order to obtain more extensive information pertaining to their suitability as the raw material for a food supplement. It was found that 100 g of the nuts consist of 1.79 g of ash, 2.08 g of moisture content, 66.78 g of crude fat, 9.07 g of total carbohydrate, 3.40 g of crude protein, 61.43 mg of iron and 103.30 mg of calcium. The oxidative stability of the nuts was studied during storage at four different conditions including 4°C, 45°C, room temperature (23-25°C) and sun light exposure. Peroxide values were measured every 30 days for 4 months. At 45°C, the peroxide values were found in the range 2.31-3.94 meq ROOH/kg of fat, which is higher than at other conditions. The nuts stored at 4°C showed the lowest peroxide value, ranging from 1.37 to 2.70 meq ROOH/kg of wax. Where as, they were 1.1446-1.1877 meq ROOH/kg of fat at room temperature. It was concluded that the preferred temperature for keeping the nuts is at 4°C. © ISHS.